Pipelined and parallel computer architectures - Sajjan G Shiva (HarperCollins, 1996)
This book is designed for a second course in computer architecture, and as such assumes a background in basic architectural concepts of single processor systems. These concepts are reviewed in the first two chapters of the book. Chapters 3 and 4 concentrate pipelined architectures. Chapters 5, 6, and 7 deal with parallel processing architectures, and Chapter 8 concludes the book with a discussion of current trends. Each chapter describes the most generic hardware aspects follewed by supporting details on corresponding programming languages, data structures, and operating systems. Each chapter also provides details of several commercially availablesystems